Administrative Control Measures in the Face of the Corona Pandemic - Al-Shammeri, Ahmed (The Arab Journal of Administration, 2022)
Administrative control is one of the most important administrative activities of the state, and it is a preventive system primarily aimed at preserving public order and maintaining basic rights and freedoms, whether under ordinary or exceptional circumstances. The state is obliged to intervene to control and combat all that affects public order, faced with the outbreak of the Coronavirus, it had to intervene by taking preventive measures to limit the spread of this epidemic to prevent public health threats and provide the necessary health care to citizens, even if this restricts their freedoms guaranteed by Law.